The Schandelah Scientific Drilling Project: a 25-million year record of Early Jurassic palaeo-environmental change from northern Germany - Schootbrugge, Bas van de; Richoz, S.; Pross, Jörg; Luppold, F. W.; Hunze, S.; Wonik, T.; Blau, J.; Meister, C.; van der Weijst, C. M. H.; Suan, G.; Fraguas, A.; Fiebig, J.; et al. (Permophiles, 2019)
With the aim to understand prolonged and repeated marine anoxia after the Triassic-Jurassic mass- extinction event, a continuously cored, 338 metre thick succession of Rhaetian to Toarcian sediments was retrieved close to the village of Schandelah near Braunschweig (Lower Saxony, northern Germany). Here, preliminary biostratigraphical, lithological, sedimentological, geochemical, and geophysical borehole data are presented and discussed. Based on the presence of ammonites, ostracods, benthic foraminifers, calcareous nannofossils, and palynomorphs, all major Late Triassic and Early Jurassic stage boundaries and many of the standard Lower Jurassic ammonite zones could be defined. The deltaic Rhaetian sand- and siltstone succession (Exter Fm) contains evidence for seismic activity probably related to large-scale geodynamic processes. The Hettangian (Lias Alpha) is represented by a thick heterolithic succession composed of shallow marine sandy and silty beds with intercalated organic-rich shale, representing deposition on a shoreface with frequent storm activity. Progressive deepening during the Sinemurian to Toarcian resulted in repeated deposition of laminated organic-rich facies. Periods of relative sea-level fall likely occurred during the Late Hettangian, the Late Sinemurian, and Early Pliensbachian, where a series of hardgrounds occur indicating erosion on the sea floor followed by sea level rise leading to omission, and increased reworking. One of the most conspicuous features of the Lower Jurassic in the Schandelah-1 core is the presence of abundant authigenic carbonates (glendonites,concretions, beef-calcite) within the Upper Pliensbachian with partly very negative C-isotope values (down to -37‰ V-PDB) suggesting the anaerobic oxidation of methane. A high-resolution organic carbon isotope record based on 485 analyses shows two major negative carbon isotope excursions (CIEs) within the lowermost Hettangian and Lower Toarcian, respectively. Both excursions coincide with the onset of black shale deposition and are well-known features of these time-intervals in other regions. Despite the fact that black shale deposition also characterizes parts of the Sinemurian and Pliensbachian in similar facies, no large negative CIEs are apparent. The Schandelah-1 core thus provides an unique archive of sedimentary, biotic and geochemical records of long-term Triassic-Jurassic palaeo-environmental change in the European Epicontinental Seaway.